Antifragile: Things That Gain from Disorder - Nassim Nicholas Taleb (New York Random House, 2012)
From the bestselling author of The Black Swan and one of the foremost philosophers of our time, Nassim Nicholas Taleb, a book on how some systems actually benefit from disorder. In The Black Swan Taleb outlined a problem; in Antifragile he offers a definitive solution: how to gain from disorder and chaos while being protected from fragilities and adverse events. For what he calls the "antifragile" is one step beyond robust, as it benefits from adversity, uncertainty and stressors, just as human bones get stronger when subjected to stress and tension. Taleb stands uncertainty on its head, making it desirable, and proposing that things be built in an antifragile manner. Extremely ambitious and multidisciplinary, Antifragile provides a blueprint for how to behave-and thrive-in a world we don't understand and which is too uncertain for us to even try to understand. He who is not antifragile will perish. Why is the city state better than the nation state, why is debt bad for you, and why is almost everything modern bound to fail? The book covers innovation, health, biology, medicine, life decisions, politics, foreign policy, urban planning, war, personal finance, and economic systems. Throughout, the voice and recipes of the ancient wisdom from Phoenician, Roman, Greek, and Medieval sources are heard loud and clear.
Keywords: Nonfiction; Philosophy; Finance; Economics; Business; Psychology